Genetic diversity and interdependent crop choices in agriculture - Brian Walker Geoffrey Heal (Fondazione Eni Enrico Mattei (FEEM), 2002)
The extent of genetic diversity in food crops is important as it affects the risk of attack by pathogens. A drop in diversity increases this risk. Farmers may not take this into account when making crop choices, leading to what from a social perspective is an inadequate level of diversity.
Keywords: 330; Genetic diversity; agriculture; Nash equilibrium; external effect; Artenvielfalt; Landwirtschaftliche Bodennutzung; Externer Effekt; Theorie; Pflanzenbauprodukt